Country virtual learning exchange workshop series: Insights from the Gambia - North, Hanna; Paez Valencia, Ana Maria (2024)
Despite constitutional provisions ensuring equal treatment and opportunities for women, implementation of these laws, particularly in rural areas governed by customary land tenure systems, often falls short. Customary and religious practices tend to favour men, with limited representation of women in positions of authority. Recognizing the institutional barriers faced by women is crucial for achieving gender equality and securing land rights.